PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP HASIL BELAJAR SISWA PADA MATERI POKOK GERAK LURUS KELAS X SEMESTER I SMA NEGERI 11 MEDAN T.A. 2014/2015 - Nurliana Nurliana; Rita Juliani (INPAFI (Inovasi Pembelajaran Fisika), 2015)
This study aims to determine the effect of problem-based learning model for student learning outcomes in the subject matter straight motion X class first semester of SMA 11 Medan T.A. 2014/2015. This research is quasi experiment. The population is the entire class X MIA semester SMA 11 Medan consists of five classes. Samples were taken two classes of grade X MIA 3 as the experimental class and class X MIA 4 as the control class, each of which consist of 40 students is determined by cluster random sampling. Both classes are given different treatment, the experimental class with problem-based learning model and grade control with conventional learning. The data used in the research is a description of the number of about 10 items that have been divalidkan. The results showed that the learning outcomes of students using problem-based learning model has increased significantly. Testing results of the study by testing the hypothesis of effect is obtained that the problem-based learning model for student learning outcomes in the subject matter straight motion X class first semester of SMA 11 Medan T.A. 2014/2015. Keywords :    problem-based learning, straight motion, student learning                        outcomes